Recent changes in the mutational dynamics of the SARS-CoV-2 main protease substantiate the danger of emerging resistance to antiviral drugs - Parigger, Lena; Krassnigg, Andreas; Schopper, Tobias; Singh, Amit; Tappler, Katharina; Köchl, Katharina; Hetmann, Michael; Gruber, Karl; Steinkellner, Georg; Gruber, Christian C. (Frontiers in Medicine, 2022)
The current coronavirus pandemic is being combated worldwide by nontherapeutic measures and massive vaccination programs. Nevertheless, therapeutic options such as SARS-CoV-2 main-protease (Mpro) inhibitors are essential due to the ongoing evolution toward escape from natural or induced immunity. While antiviral strategies are vulnerable to the effects of viral mutation, the relatively conserved Mpro makes an attractive drug target: Nirmatrelvir, an antiviral targeting its active site, has been authorized for conditional or emergency use in several countries since December 2021, and a number of other inhibitors are under clinical evaluation. We analyzed recent SARS-CoV-2 genomic data and discovered accelerated mutational dynamics in an eight-residue long consecutive region (R188-G195) near the active site of Mpro since early December 2021. The herein described increased mutational variability in close proximity to an antiviral-drug binding site may suggest the onset of the development of antiviral resistance. This emerging diversity urgently needs to be further monitored and considered in ongoing drug development and lead optimization.